‘The patient is my space’: hermeneutic investigation of the nurse-patient relationship in critical care - Papathanassoglou, Elizabeth; Vouzavali, Foteini; Karanikola, Maria (My University, 2011)
Background: The nurse-patient relationship has been postulated to lie at the core of nursing care. However, it is unclear how this concept applies in critical care, as a great majority of critically ill patients are unable to communicate. Aims: Through a phenomenological hermeneutical perspective, we aimed to explore intensive care nurses' perceptions and meanings regarding their interpersonal relationship with critically ill individuals. Methods: A Heideggerian hermeneutical approach was used to design the study and analyse the data, which were collected through repetitive interviews with 12 intensive care nurses. Results: Critical care nurses report to experience deep relationships with patients, which seem to be mediated by the ongoing contact with patients' bodies. These relationships evoke intense feelings of love, empathy and care and affect how nurses perceive and make sense of their role and their world. The identified core theme of their experience is entitled ‘syncytium’, which describes a network of closely connected cells. According to participants' perceptions, nurse and patient affect each other reciprocally and are mutually dependent upon each other. In Heideggerian terms patients provide nurses with opportunities to experience ‘authentic care’ and they participate in their ‘being-in-the-world’, thus they are central in nurses' meanings about their role and existence. Other elicited themes that account for the perceived nurse-patient relationship include the spatiality/temporality of the relationship, nurses' perceptions and meanings attributed to their role and nurses' perceptions of death. Conclusions: Critical care nurses appear to experience their relationships with patients intensely. These relationships are invested with meanings and elicit powerful feelings over a shared course with patients. Patients are central in nurses' meaning-making process and role perception. Relevance to clinical practice: These findings have implications for the educational preparation of critical care nurses and their psychological support
Keywords: Interpretative research; Intensive care nurses